Compounds in Human Body Organic - Noora falah abd al hassn; Hanan Ayoub Hussein Mutar; Naba yaseen Mahmoud Farhan; Rasul Hamed Kareem Muhammad; Riyam ali hassan shaker (Genius Journals, 2024)
This research includes an introduction to organic chemistry in the human body, compounds, their importance, composition, types and presence , the functional group is a group of atoms linked by strong covalent bonds and tending to function in chemical reactions as a single unit. You can think of functional groups as tightly knit “cliques” whose members are unlikely to be parted. Five functional groups are important in human physiology; these are the hydroxyl, carboxyl, amino, methyl and phosphate groups
Keywords: Compounds; Human Body; Organic